Isolated Memory Loss in Anti-NMDAR Encephalitis. Issue 2 (March 2022) - Iorio, Raffaele; Sabatelli, Eleonora; Campetella, Lucia; Papi, Claudia
Abstract : Background and Objectives: To report a case of anti-NMDAR encephalitis presenting with isolated memory dysfunction. Methods: A 29-year-old woman was admitted to the Neurology Department referring memory impairment with a subacute onset. The initial assessment included EEG, neuropsychological tests, and brain MRI. Serum and CSF samples were collected for immunologic studies. The diagnostic evaluation was completed with a total body PET scan. Results: Patient's neurologic examination was unremarkable apart from an episodic memory deficit, confirmed by neuropsychological examination. The EEG revealed epileptiform discharges in the temporal lobes, whereas brain MRI showed bilateral temporal lobes hyperintense lesions on fluid-attenuated inversion recovery images and T2-weighted images. NMDAR-IgG was detected in the patient's serum and CSF by cell-based assay confirming the diagnosis of definite anti-NMDAR encephalitis. The total body PET showed only a slight hypometabolism in the right temporal cortex and in the cerebellar hemispheres. After a course of IV immunoglobulin and corticosteroid therapy, a marked improvement of the memory deficit was observed. Discussion: This case shows that anti-NMDAR encephalitis can present with isolated memory loss. Neural antibody testing in these patients could play a pivotal role in early diagnosis and prompt treatment.